Bioequivalence Studies of Tacrolimus Capsule under Fasting and Fed Conditions in Healthy Male and Female Subjects - Lainesse, Audrey; Hussain, Saleh; Monif, Tausif; Reyar, Simrit; Tippabhotla, Sudhakar Koundinya; Madan, Ashish; Thudi, Nageshwar Rao (Arzneimittelforschung, 2008)
The bioequivalence of tacrolimus (CAS 104987–11–3) 5 mg capsules was assessed in two single-dose, open-label, randomized 2-way crossover trials with a minimum washout period of 14 days; one trial was conducted under fasting condition (n = 44) and the other one under fed condition (n = 48). Blood samples were collected over a 120-h period and concentrations were assayed using a liquid chromatography tandem mass spectrometry (LC-MS/MS) method. A non-compartmental method was used for calculation of pharmacokinetic parameters. Under fasting conditions, mean AUC0–t, AUC0–inf and Cmax were comparable between the test (296 ng · h/mL, 318 ng · h/mL and 32 ng/mL, respectively) and the reference formulations (289 ng · h/mL, 309 ng · h/mL and 33 ng/mL, respectively). Tmax was reached between 1.5 and 2 h post-dose. Mean AUC0–t, AUC0–inf and Cmax were also comparable under fed conditions (154 ng · h/mL, 169 ng · h/mL and 7.6 ng/mL, respectively, for the test and 161 ng · h/mL, 176 ng · h/mL and 7.5 ng/mL, respectively, for the reference formulation). Under fed conditions, Tmax was reached between 5 and 6 h post-dose. 90 % geometric confidence intervals were all within the acceptable 80–125% limit, suggesting bioequivalence between the generic product and the innovator product.
Keywords: CAS 104987–11–3; Immunosuppressants; Tacrolimus, bioequivalence, fasting and fed condition, male and females volunteers, pharmacokinetics